Safe Injection Practices and Awarness among Health Care Workers in Tertiary Level Hospitals Kathmandu, Nepal - Bhandari, Tulsi Ram (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Blood-borne diseases; Infection prevention; Needle stick injury; Universal precaution. DOI: 10.3126/jnhrc.v6i1.2440 Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 22-27